Human Characteristics in the Quran: Cultivating the Virtue of Humility Through An Environmental Reading of the Quran Exegesis - Masoud Shavarani (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2025)
Environmental advocates have challenged and criticized the anthropocentric doctrines present in Abrahamic religions, including Islamic theology. The term “human” (“al-insān” in Arabic) holds significance in defining the human’s place in nature, as depicted in various Quranic verses where it is frequently associated with blameworthy characteristics. In these verses, the Quran always reminds human weaknesses and powerlessness. The characteristics used to describe humans in the Quran include: weak (ḍaʿīf), despondent (yaʾūs), ungrateful (kafūr), vain (fariḥ), braggart (fakhūr), hopeless (qanūṭ), niggardly (qatūr), covetous (halūʿ), apprehensive (jazūʿ), grudging (manūʿ), in loss (khusr), unthankful (kanūd), disputatious (jadal), rebellious (ṭughyān), overhasty (ʿajūl), in delusion (ghurūr), laborious (kādiḥ), in travail (kabad), the lowest of the low (asfal sāfilīn), dry clay (ṣalṣāl), aging mud (ḥamaʾ masnūn), and denier of the resurrection. The word “insān” in the Quran is never associated with praiseworthy human characteristics. The negative attributes associated with this term imply the significance of humility, humbleness, and discourage arrogance and grandiosity. These teachings serve as an invitation for individuals to refrain from asserting dominance or superiority over others, including other beings in nature. Instead, the emphasis is placed on embracing the ethics of servitude and humility.